Mitochondrial Inner Membrane Depolarization as a Marker of Platelet Apoptosis: Disclosure of Nonapoptotic Membrane Depolarization. (March 2017) - Gyulkhandanyan, Armen V.; Allen, David J.; Mykhaylov, Sergiy; Lyubimov, Elena; Ni, Heyu; Freedman, John; Leytin, Valery
Availability of universal marker for the diagnosis of platelet apoptosis is an important but currently unresolved goal of platelet physiology investigations. Mitochondrial inner transmembrane potential (▵Ψm) depolarization is frequently used as a marker of apoptosis in nucleated cells and anucleate platelets. Since ▵Ψm depolarization in platelets is also frequently associated with concurrent induction of other apoptotic responses, it may appear that ▵Ψm depolarization is a good universal marker of platelet apoptosis. However, data presented in the current study indicate that this is incorrect. We report here fundamental differences in the effects of potassium ionophore valinomycin and calcium ionophore A23187 on human platelet apoptosis. Although both A23187-triggered and valinomycin-triggered ▵Ψm depolarization are strongly induced, the former is dependent on the opening of mitochondrial permeability transition pore (MPTP) and the latter is MPTP-independent. Furthermore, effects of calcium and potassium ionophores on other apoptotic events are also basically different. A23187 induces caspase-3 activation, proapoptotic Bax and Bak protein expression, phosphatidylserine exposure, and microparticle formation, whereas valinomycin does not induce these apoptotic manifestations. Discovery of targeted ▵Ψm depolarization not associated with apoptosis in valinomycin-treated platelets indicates that this marker should not be used as a single universal marker of platelet apoptosis in unknown experimental and clinical settings as it may lead to a false-positive apoptosis diagnosis.